Multiple Methods for Identifying Outcomes of a High Challenge Adventure Activity. (June 2016) - Davidson, Curt; Ewert, Alan; Chang, Yun
The purpose of this study was to provide insight into what occurs in moments of high challenge within participants during an outdoor adventure education (OAE) program. Given the inherent risk and remote locations often associated with OAE programs, it has remained challenging to measure selected psychological constructs while the program is taking place. This study utilized qualitative methods including in situ data collection techniques and quantitative inquiry methods to identify and determine what is happening to participants before, during, and after a high challenge activity—rappelling. The results of this study identified five salient themes that emerged as important constructs for OAE participants and are useful to consider as researchers and OAE practitioners design and implement high challenge activities. Further analysis and discussion about the importance of these themes are discussed at length.